Analisis Perspektif Pengguna Terhadap Website Faculty of Communication, Visual Art and Computing (FCVAC) Menggunakan Teknik Systyem Usability Scale (SUS) - Nia Adila; Putri Melani; Novia Sukma (APTIKOM SUMSEL, 2020)
This practical work aims to evaluate and assess the level of user usefulness at the Universiti Selangor Faculty of Communication, Visual Art and Computing (FCVAC) website. The method used in collecting data needed in writing this practical work report is to use a questionnaire created in accordance with the System Usability Scale (SUS) technique filled out online using Google Form, while the writing technique uses descriptive techniques. And based on the observation of the author during practical work on the use of users on the website of the Faculty of Communication, Visual Art and Computing (FCVAC) Universiti Selangor, its usability can be accepted by the user so that the website can be used properly